SOCIOCULTURAL CHARACTERISTICS OF THE COSSACKS - Kotovchikhina, Natalia; Kuraev, Alexey; Polozhentseva, Irina; Emtseva, Olga; Abeldinova, Ekaterina (Revista Inclusiones, 2020)
Cossacks are a unique ethnic and sociocultural phenomenon in history. Cossacks were not only a social condition with a special way of life and an original military formation but a unique model of social development with an original sociopolitical structure, a peculiar way of life, traditions, ethical and legal norms and institutions, culture and folklore. Based on an expert survey, the fundamental sociocultural characteristics of the Cossacks have been determined, to which the sovereignty of the Russian Cossacks, their mission, consisting of a buffer (border) role and the protection of the fatherland, freedom and Cossack democracy as imperatives of life, as well as the specifics of mentality and ethnopsychological characteristics of the Cossacks have been attributed.